Aplicação da norma IEC 61400-25 na automação e controle de parques eólicos no Brasil - Celino, Ronaldo Andrusyszyn (2017)
The goal of this project is to develop a system of supervision, communication and control, implemented in a free supervisory software the SCADABR for installed wind farms and/or to be installed in Brazil, from the considerations and recommendations of IEC 61400 - 25. The construction of complete wind farms with full automation, has led entrepreneurs to focus their efforts not only on profit and productivity, but also in: human capital, concerned with the management system, technological mastery and communication at all levels. Information processing with communication, opened borders with new forms of relationship and growing trend in the industrial automation field, which favors different devices to communicate with others in a cooperative way. However, the largest manufacturers of wind generation plants still offer proprietary solutions "black boxes" for the networks field, which results in a variety of protocols of systems, causing the client the full dependence on these suppliers. Aiming interoperability and flexibility of operation, groups of researchers advocate standards of open model, as the solution of networks and protocols for all, leaving customers free. In this struggle, the best-known organization in the field of wind energy is IEC 61400-25, specifically for the monitoring system and free communication among different equipment vendors, nevertheless internal communication of the components of wind power plant is not within the standard. The application range of the standard covers the operation of this kind of wind farm, including wind turbine, meteorological measurement system, electrical system and management system, but does not include the relevant line of the substation feeding and information. Hence, the interaction with the supervisory system SCADABR developed in "open-source" model of free license. It is proposed the application of a multi-platform Java-based, from an application server, like Apache Tomcat the standard choice. Considering the requirements of the present communication model in IEC 61400-25-2 it is defined a model of information for monitoring and control of wind power plants, to this end, part-data simulator MatrikonOPC through customer / OPC DA server interaction (Object Linking and Embedding for Process Control Data Access), with ScadaBR software.